Exposure to point-of-sale displays and changes in susceptibility to smoking: findings from a cohort study of school students - Bogdanovica, Ilze; Szatkowski, Lisa; McNeill, Ann; Spanopoulos, Dionysis; Britton, John (Wiley, 2015)
Aims